Two new species of zooplanktivorous haplochromine cichlids from Lake Victoria, Tanzania - de Zeeuw, Marnix P. (Pensoft Publishers, 2013)
Abstract. Two new species of zooplanktivorous haplochromine cichlids from Lake Victoria, Tanzania, are described and illustrated. These species closely resemble each other. Their affinities to other zooplanktivorous haplochromines from Lake Victoria are discussed. Haplochromis argens sp. n., which featured under nicknames (mainly Haplochromis “argens”) in more than 50 papers, was caught both in the Mwanza Gulf and the Emin Pasha Gulf, whereas Haplochromis goldschmidti sp. n. was only found in the Emin Pasha Gulf. Of the latter species only males are available, but it seems unlikely that it represents a case of male colour polymorphism as several presumably unrelated characters differ in sympatry between the two species, suggesting that there is no gene flow. Statistical analysis revealed that the overall difference between the two species is greater than that between the populations from the two locations. Body depth of the two species in sympatry in the Emin Pasha Gulf was more similar than that of Haplochromis goldschmidti sp. n. and the allopatric population of Haplochromis argens sp. n. from the Mwanza Gulf,which mayindicate an overall environmental effect. However, several measurements related to the width of snout and mouth differed more between the populations of the two species in sympatry than between the allopatric populations. In contrast to a group of zooplanktivorous species that recovered successfully after environmental changes in the lake, Haplochromis argens sp. n. is among a group that became extremely rare and probably is in danger of extinction; the conservation status of Haplochromis goldschmidti sp. n. is currently unknown.